Cultural Knowledge and Social Inequality - Lareau, Annette (American sociological review, 2015)
Using both qualitative longitudinal data collected 20 years after the original Unequal Childhoods study and interview data from a study of upwardly mobile adults, this address demonstrates how cultural knowledge matters when white and African American young adults of differing class backgrounds navigate key institutions. I find that middle-class young adults had more knowledge than their working-class or poor counterparts of the "rules of the game" regarding how institutions worked. They also displayed more of a sense of entitlement to ask for help. When faced with a problem related to an institution, middle-class young adults frequently succeeded in getting their needs accommodated by the institution; working-class and poor young adults were less knowledgeable about and more frustrated by bureaucracies. This address also shows the crucial role of "cultural guides" who help upwardly mobile adults navigate institutions. While many studies of class reproduction have looked at key turning points, this address argues that "small moments" may be critical in setting the direction of life paths.